The Influence of Promotion Approach and Store Layout on Impulse Buying Behavior - Jhanghiz Syahrivar (President University, 2016)
This research aimed to determine factors which influenced impulse buying behavior at one of local clothing retail store in Cikarang. Based on the previous studies, Promotion Approach and Store Layout were hypothesized as the independent variables which influenced Impulse Buying Behavior as the sole dependent variable. The researcher employed SPSS and binomial logistic regression to analyze the data collected from questionnaires spread to 200 customers of the local clothing retail store. The result of this research suggested that Promotion Approach and Store Layout significantly influenced Impulse Buying Behavior. The biggest influencer to Impulse Buying Behavior was Promotion Approach.